Evaluation of Bile Duct Injury Managements: Surgery and Endoscopy - Dedy Chandra Hariyono; Anung Noto Nugroho (Jurnal Kesehatan dan Kedokteran, 2025)
Bile duct injuries (BDI) are serious complications following cholecystectomy, requiring careful management to ensure optimal outcomes. This study compares biliodigestive surgery and minimally invasive procedures, including ERCP, PTBD, and EUS-BD, to guide clinical decision-making. A retrospective analysis was conducted on 44 patients who experienced BDIs post-cholecystectomy from January 2023 to February 2025. Patients were grouped based on their treatment modality, and outcomes were assessed in terms of recovery time, complications, and long-term functional results. Statistical analyses using the SPSS Chi-Square test were performed to evaluate differences between the two groups. Among the 44 patients, 10 died, while 34 clinically improved. ERCP emerged as the most successful minimally invasive procedure, with 20 successful interventions and only 5 failures. PTBD and EUS-BD showed moderate success, while biliodigestive surgery had a higher failure rate, with 8 out of 12 procedures unsuccessful. However, the statistical analysis revealed no significant correlation between treatment modality and improved clinical outcomes. In conclusion, while minimally invasive procedures, particularly ERCP, offer lower morbidity and faster recovery, they do not demonstrate a statistically significant advantage over surgical interventions in terms of overall clinical outcomes. Biliodigestive surgery remains essential for managing complex injuries. Therefore, treatment selection should be tailored based on injury severity and individual patient conditions, emphasizing the importance of personalized treatment strategies.